High performance embedded architectures and compilers : Third International Conference, HiPEAC 2008, Göteborg, Sweden, January 27-29, 2008 : proceedings - Hutchison, David; Kanade, Takeo; Kittler, Josef; Gupta, Rajiv K; Ungerer, Theo (Lecture Notes in Computer Science, 2008)
This book constitutes the refereed proceedings of the Third International Conference on High Performance Embedded Architectures and Compilers, HiPEAC 2008, held in G??teborg, Sweden, January 27-29, 2008. The 25 revised full papers presented together with 1 invited keynote paper were carefully reviewed and selected from 77 submissions. The papers are organized in topical sections on Multithreaded and Multicore Processors, Reconfigurable - ASIP, Compiler Optimizations, Industrial Processors and Application Parallelization, Power-Aware Techniques, High-Performance Processors, Profiles: Collection and Analysis as well as Optimizing Memory Performance.